Implementasi Kurikulum Merdeka Belajar Dalam Proses Pengembangan Kemandirian dan Kreatifitas di Taman Kanak-Kanak Kecamatan Juwana - Hardiyani, Ita Kris; Diana; Hartono (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Based on preliminary observations at Juwana District Kindergarten, most of the learning process still focuses a lot on students' cognitive abilities so that students' independence and creativity are less developed. This study aims to determine the effect of implementing the Merdeka Curriculum on students' independence and creativity in kindergartens in Juwana District. This research is qualitative research. Research data were obtained through observations and interviews with principals, teachers, and parents of students. The results showed that the Merdeka curriculum has been implemented in Juwana District Kindergarten with a learning process tailored to the needs of students, creativity, and innovation in accordance with the objectives of the independent curriculum in accordance with applicable regulations. The implementation of the Merdeka Curriculum in Juwana District Kindergarten and the role of parents at home greatly help the development of early childhood independence so that the level of independence and creativity of students is mostly in the developing as expected category. These results indicate that the implementation of the independent curriculum has an effect on the development of students' independence and creativity in kindergartens in Juwana District.